The Use of Visual Picture in Increasing Students’ Writing Skill At the Ninth Grader of MTs NW No. 2 Rensing In the School Year 2022/2023 - Karomi Safari, M. Ubaidillah (FAKULTAS TARBIYAH, 2022)
This study focused to know the effectiveness of using visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing. to what extent the effectiveness of using visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing. This was an experimental study. It consisted of two groups by 32 students divided into students as experimental and as control group. I used writing test in assessing students’ writing skill through visual picture and hypothesis testing. Result showed that mean score in pre-test and post-test for the experimental group was 60.56 and 65.13. Indeed, based on the result of hypothesis at the level of significance a = 0.05, I found that t-test > table were 5.18 > 2.048. Hypothesis was accepted. It means there was a significant effect of visual picture in increasing students’ writing skill at the ninth grader of MTs NW No. 2 Rensing in the school year 2022/2023.